Helium and hydrogen effects in structural materials for nuclear applications - Karpov, S.A.; Tolstolutska, G.D. (Вопросы атомной науки и техники, 2022)
Displacement cascades produce a variety of defects under reactor conditions, but of particular concern is the simultaneous production of helium (He) and hydrogen (H), which enhances the degradation of structural materials. The overall majority of performed studies on helium and hydrogen interactions with materials were based on ion beam irradiation, which served as a convenient tool for the simulation of neutrons exposure over a variety of temperature and dose regimes due to the ability to widely vary and control the irradiation parameters. Experimental investigations of the hydrogen-defect interaction performed by thermal desorption spectroscopy, and the parameters of this interaction obtained by numerical simulations based on diffusion-trapping codes are debated. In this review, we also summarize previous studies on grain boundaries and nanoprecipitate effects on hydrogen transport in metals, as well as the role of hydrogen in the corrosion and cracking of steels. We discuss here issues of helium bubbles formation and some of the evidence for the synergistic effects of hydrogen and helium in the presence of displacement damage, and their influence on irradiation hardening and swelling. Particular attention was devoted to the features of hydrogen interaction with noble-gas bubbles, which were considered on the basis of most recent published data. У реакторних умовах каскади зміщення генерують безліч радіаційних дефектів, але особливе занепокоєння викликає одночасне утворення гелію (He) та водню (H), які посилюють деградацію конструкційних матеріалів. Переважна більшість виконаних досліджень щодо взаємодії гелію та водню з матеріалами заснована на іонно-пучковому опроміненні, яке є зручним інструментом для моделювання впливу нейтронів у різних температурних та дозових режимах завдяки можливості широко варіювати та контролювати параметри опромінення. В огляді обговорюються експериментальні дослідження взаємодії водень-дефект, виконані методом термодесорбційної спектроскопії, а також параметри цієї взаємодії, отримані шляхом чисельних розрахунків, заснованих на моделюванні дифузійного захоплення. Ми також узагальнюємо попередні дослідження з вивчення впливу меж зерен та нанопреципітатів на перенесення водню в металах, а також впливу водню на корозію та розтріскування сталей. Крім того, обговорюються питання утворення бульбашок гелію та деякі свідчення синергетичного ефекту водню та гелію у присутності пошкоджень зміщення, а також їх вплив на радіаційне зміцнення та розпухання. Особливу увагу приділено особливостям взаємодії водню з бульбашками інертних газів, розглянутим з урахуванням останніх опублікованих даних.